Use of Facebook and the self perception of body image in women - Infante Faura, Jazmin del Rosario (2017)
The present research is a quantitative study and an applied, transversal and descriptive correlational study about the use of Facebook and self - perception of the body image in a group of university students. The purpose was to determine the relationship between the use of Facebook and self-perception of the body image. For this case it was used a scale that measured the used of Facebook and a body shape questionnaire. These were applied to 106 students whose ages ranged from 17 to 24 years old, from the first, fifth and tenth semester of the undergraduate department of Psychology and Communications from a Private University of Lima Metropolitana. The results show a positive and significant relationship between the use of Facebook and negative self-perception of body image in women (r=0.247; p<0.05).